Anthropology and Medical Photography: Ethnographic, Critical and Comparative Perspectives. Issue 2 (14th March 2016) - Lynteris, Christos; Prince, Ruth J.
Abstract : The study of medical photography, inclusive of epidemiological and humanitarian applications of the genre, is a promising new field for visual anthropology. Focusing on the interlinked questions of visual witnessing and evidential ethics of medical photography, as well as on the entangled temporalities and dialectics of visibility and invisibility underlying this visual practice, the introduction to this special issue on medicine, anthropology and photography explores key issues arising out of recent work in the area. While reviewing the contributions of history, STS and photographic theory to the study of medical visual cultures, regimes and economies, we explore what a distinctively anthropological approach—through its ethnographic and comparative scope—offers to the topic.